2014
DOI: 10.1016/j.vaccine.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus diversity among diarrheal children in Delhi, India during 2007–2012

Abstract: Rotavirus is the leading cause of severe gastroenteritis in young children worldwide and is responsible for around 100,000 deaths in India annually. Vaccination against rotavirus (RV) is a high priority: 'ROTAVAC' an indigenous vaccine will soon be licensed in India. Surveillance to determine the impact of vaccines on emerging RV strains is required. In this study we compared the pattern of RV strains circulating in Delhi over a 5 year period with the strains over the past 12 years. The most commonly detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…A written informed consent was obtained from one of the parents of the child before enrollment. All (350) children with diarrhea of less than 3 days duration were screened for group A rotavirus [17]. The remaining group A rotavirus (RV) negative (180) fecal specimens were stored in a deep freezer (−80 °C) for further testing.…”
Section: Methodsmentioning
confidence: 99%
“…A written informed consent was obtained from one of the parents of the child before enrollment. All (350) children with diarrhea of less than 3 days duration were screened for group A rotavirus [17]. The remaining group A rotavirus (RV) negative (180) fecal specimens were stored in a deep freezer (−80 °C) for further testing.…”
Section: Methodsmentioning
confidence: 99%
“…These RVA G9P[8] strains have been under circulation and found to cause symptomatic infections among children <5 years of age, who were expected to be protected by the pre‐existing immunity which would provide heterotypic protection against common genotypes . Over the years, G9 RVA strains are under circulation worldwide including India …”
Section: Introductionmentioning
confidence: 99%
“…24 Over the years, G9 RVA strains are under circulation worldwide including India. [25][26][27][28][29] In India, surveillance studies conducted on rotavirus disease and the genotype distribution of these strains reported over the years have revealed that G9 RVA genotype is circulating since 1994 in different geographical regions. 26,[28][29][30][31] Recent studies have documented proportion of RVA infections with G9 strains at 13-40% level in acute gastroenteritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For children under 5 years of age, 1700 000 000 episodes of diarrhea are seen worldwide, and death occurs in 700 000 of these cases due to diarrhea . Furthermore, rotavirus is an important cause of diarrhea in this age group . Vitamin D is a fat‐soluble vitamin that is produced in the skin when sunlight is absorbed.…”
mentioning
confidence: 99%